Climate change 1995 : the science of climate change - Houghton, J.T. ed. ...[et al] (CUP CambridgeGB, 1996)
Deals with the physical climate system, the factors that drive climate change, analyses of past climate and projections of future climate change, and detection and attribution of human influence on recent climate.